Analysis of sugar content in formula foods and complementary foods for infants and young children aged 0-36 months in China - LIU Sana; WANG Qihe; LI Guohui; FU Wenli; LIANG Dong; FANG Haiqing (Zhongguo shipin weisheng zazhi, 2023)
ObjectiveTo investigate the implementation of the standards （formula foods and complementary foods for infants and young children）， the contents of glucose， galactose， fructose， lactose， sucrose and maltose in formula foods and complementary foods for infants aged 0-36 months， and provide data support for the management of food safety standards related to infant formula and infant complementary food in China.MethodsBased on the principle of random sampling， 83 formula food and complementary food for infants and young children， including infant formula foods， older infant formula foods， young children formula foods， cereal complementary foods and canned foods for infants and young children， were collected from the domestic market， the content of glucose， galactose， fructose， lactose， sucrose and maltose were determined by ion chromatography-pulse ampere method and the results were analyzed.ResultsThe median of total sugar content in formula foods for infants and young children was 433.43-476.99 g/kg； the proportion of lactose in all kinds of products was higher than 95%， and the content from high to low was infant formula， older infant formula and formula for young children. The detection rate of sugar in infant cereal supplementary food was 36.8%， the median content was 0-28.35 g/kg； the medians of lactose and sucrose were 84.30 and 70.17 g/kg； while the third quartile（Q3） of sucrose was 53.43 g/kg. There was no significant difference in the content of added sugar between domestic and imported formula foods（P>0.05）.ConclusionThe lactose content in formula foods for infants and young children sold in China is higher than that of other sugars. The content of total sugar in cereal supplementary food is low， but the content of sucrose in biscuit should be concerned. It is suggested that enterprises should strictly control added sugar， and government departments should continue to push the implementation of the sugar content regulation in the newly released national standards.